Adaptive Education as a Key Element for Enhancing the Effectiveness of Learning Processes - S. M. Levin; A. I. Isakova (Цифровая трансформация)
This article explores issues related to the adaptive learning of students in higher education institutions, presenting the main characteristics of both traditional and contemporary educational paradigms. It describes the latter’s advantages in the context of the dynamic changes of the modern world and, specifically, the demands on the process and outcomes of higher education. In discussing modern learning concepts, those foundational to adaptive learning are examined separately. The authors provide a description, objectives, methods, and results of the study conducted as an experiment with first-year undergraduate students. The results are assessed in the conclusion, and recommendations for their practical application are presented.